A revision of Scipopus Enderlein including the subgenera Scipopus s. str., Phaeopterina Frey and Parascipopus subgen. nov. (Diptera, Micropezidae, Taeniapterinae) - Lindsay, Kate; Marshall, Stephen A. (European Journal of Taxonomy, 2023)
The genus Scipopus (Diptera, Micropezidae, Taeniapterinae) is redefined and revised to include the genera previously treated as the “Scipopus group” which included Scipopus Enderlein, Pseudeurybata Hennig, and Phaeopterina Frey. Pseudeurybata is treated as a junior synonym of Phaeopterina and the genus Scipopus is redefined to include three subgenera: Scipopus s. str., Phaeopterina and Parascipopus subgen. nov.. Redescriptions of 18 previously described species, and descriptions of 25 new species are provided as follows: S. (Parascipopus) subgen. nov., S. (Parascipopus) alturas sp. nov., S. (Parascipopus) fenestratus sp. nov., S. (Parascipopus) kubus sp. nov., S. (Parascipopus) monteverde sp. nov., S. (Parascipopus) nigriscapus sp. nov., S. (Parascipopus) otisi sp. nov., S. (Parascipopus) savegre sp. nov., S. (Parascipopus) tico sp. nov., S. (Phaeopterina) argentum sp. nov., S. (Phaeopterina) brunneus sp. nov., S. (Phaeopterina) lineatus sp. nov., S. (Phaeopterina) musculosus sp. nov., S. (Phaeopterina) narupa sp. nov., S. (Phaeopterina) noturgidus sp. nov., S. (Phaeopterina) turgidus sp. nov., S. (Phaeopterina) vee sp. nov., S. (Phaeopterina) fraudator sp. nov., S. (Phaeopterina) metallicus sp. nov., S. (Phaeopterina) quetzal sp. nov., S. (Phaeopterina) uniformis sp. nov., S. (Scipopus) brikelos sp. nov., S. (Scipopus) convexus sp. nov., S. (Scipopus) nitidus sp. nov., S. (Scipopus) planus sp. nov., and S. (Scipopus) wokomung sp. nov. Scipopus (Scipopus) limbativertex Enderlein is a new junior synonym of S. (Scipopus) nigripennis (Hendel), S. (Scipopus) bolivianus Hennig is a new junior synonym of S. (Scipopus) belzebul (Schiner), S. (Scipopus) frit Cresson is a new junior synonym of S. (Scipopus) calocephalus (Bigot) and S. (Scipopus) alvarengai Albuquerque is a new junior synonym of S. (Scipopus) erythrocephalus (Fabricius). The phylogeny of Scipopus s. lat. and its presumed outgroup (a clade containing Rainieriella Aczel) is considered using morphological and molecular data and supported with a maximum likelihood tree for the genes 12S, 28S and COI.